A Systematic Review on Balance Performance in Patients With Bilateral Vestibulopathy. Issue 9 (4th May 2020) - Herssens, Nolan; Verbecque, Evi; McCrum, Christopher; Meijer, Kenneth; van de Berg, Raymond; Saeys, Wim; Vereeck, Luc; Van Rompaey, Vincent; Hallemans, Ann
Abstract: Objective: Patients with bilateral vestibulopathy (BVP) have severe balance deficits, but it is unclear which balance measures are best suited to quantify their deficits and approximate the diversity of their self-reports. The purpose of this study was to explore measures of balance control for quantifying the performance of patients with BVP related to different balance domains, allowing targeted assessment of response to intervention. Methods: MEDLINE, Web of Science, and Embase were systematically searched on October 9, 2019. The Scottish Intercollegiate Guidelines Network checklist for case-control studies was applied to assess each individual study's risk of bias. Standardized mean differences (SMD) were calculated based on the extracted numeric data and reported according to the type of sensory perturbation in the balance tasks. Results: Twelve studies (1.3%) met the eligibility criteria and were analyzed, including data of 176 patients with BVP, 196 patients with unilateral vestibulopathy, and 205 healthy controls between 18 and 92 years old. In general, patients with BVP were either unable to maintain (or had reduced) balance during tasks with multisensory perturbations compared with healthy controls (range of mean SMD = 1.52–6.92) and patients with unilateral vestibulopathy (range of absolute mean SMD = 0.86–1.66). Conclusions: During clinical assessment to quantify balance control in patients with BVP, tasks involving multisensory perturbations should be implemented in the test protocol. Impact: As patients with BVP show difficulties with movement strategies, control of dynamics, orientation in space, and cognitive processing, clinicians should implement these aspects of balance control in their assessment protocol to fully comprehend the balance deficits in these patients.